Structures of bacterial RNA polymerase complexes reveal mechanisms of DNA loading and transcription initiation - Glyde,R; Ye,F; Jovanovic,M; Kotta-Loizou,I; Buck,M; Zhang,X (Molecular Cell, 2018)
Gene transcription is carried out by multi-subunit RNA polymerases (RNAP).Transcription initiation is a dynamic multi-step process that involves the opening of the double stranded DNA to form a transcription bubble and delivery of the template strand deep into the RNAP for RNA synthesis. Applying cryo electron microscopy to a unique transcription system using 54 (N), the major bacterial variant sigma factor, we capture a new intermediate state at 4.1 Å where promoter DNA is caught at the entrance of the RNAP cleft. Combining with new structures of the open promotercomplex and an initial de novo transcribing complex at 3.4 and 3.7 Å respectively, our studies reveal the dynamics of DNA loading and mechanism of transcription bubble stabilisation that involves coordinated, large scale conformational changes of the universally conserved features within RNAP and DNA. In addition, our studies reveal a novel mechanism of strand separation by 54.